Image Improvement of the State Islamic University (UIN) Alauddin Makassar through the Satisfaction and Trust of Stakeholder on Graduate Quality - Murtiadi Awaluddin (Integrated Journal of Business and Economics (IJBE), 2018)
This study aims to determine and analyze the influence of UIN Alauddin Makassar graduate quality to stakeholder satisfaction, stakeholder trust and image of UIN Alauddin Makassar either directly or indirectly. This study categorized in exploratory research. This research included in the descriptive research. The population of this research is all stakeholders in Makassar City. The sampling technique used in this research is purposive sampling. The sample criterion used is a private banking company that employs UIN Alauddin Makassar graduates. The sample size uses maximum likelihood (ML). The number of samples in this study is 100 respondents. In this study, the techniques used include (1) questionnaire; (2) observation; (3) interviews and (4) documentation. The method of analysis used in this research is structural equation modelling (SEM) analysis. The conclusion of this research are: (1) the quality of UIN Alauddin Makassar graduates has a positive and significant impact on stakeholder satisfaction, stakeholder trust and image of UIN Alauddin Makassar; (2) stakeholder satisfaction has a positive and significant impact on stakeholder trust and image of UIN Alauddin Makassar and (3) stakeholder trust have positive and significant impact on UIN Alauddin Makassar image.